Rethinking Brain Cancer Therapy: Tumor Enzyme Activatable Theranostic Nanoparticles - Heike E. Daldrup-Link MD, PhD (Molecular Imaging)
This invited commentary discusses a recent article by Mohanty et al in Molecular Cancer Therapeutics about significant therapeutic efficacies of novel theranostic nanoparticles (TNPs) for the treatment of human brain cancers in mouse models. The TNPs were cleaved by enzymes in the tumor tissue, matrix metalloproteinase (MMP-14), which lead to release of a highly potent therapeutic drug, azademethylcolchicine. Data showed that the TNPs caused selective toxic effects in MMP-14-expressing glioblastoma and not normal brain. In addition, the iron oxide nanoparticle backbone enabled in vivo drug tracking with magnetic resonance imaging (MRI). This commentary discusses previous efforts of MMP-targeted therapeutics as well as opportunities for further refinements of tumor enzyme-activatable TNPs. If successfully translated to clinical applications, the TNPs might hold substantial potential to improving cytotoxic indexes and long-term outcomes of patients with brain cancer compared to standard therapy.